The Degree of the Practice of Ethical Leadership by the Managers of Basic Education Schools in Damascus According to Some Variables (Journal of Hama University, 2020)
The aim of the research is to identify the degree of ethical leadership practice by a sample of principals of basic education schools in Damascus city and the impact of gender variables and years of experience and scientific qualification in that. In order to achieve the objectives of the research, the researcher prepared a measure of the degree of ethical leadership practice (a) divided into four axes. After judging and confirming its statistical characteristics, it was applied to a random sample of the principals of basic education schools in Damascus.The results showed that the degree of the practice of moral leadership by the principals of the schools of the first cycle of basic education in each of the four axes, and in the overall score of the scale came to a medium degree. The results also showed no statistically significant difference between the degrees of managers and the degrees of female managers in the degree of ethical leadership practice due to the gender variable. While there was a difference between the degrees of managers in the practice of ethical leadership for managers with experience of nine years or less, in addition to a significant difference between the grades of managers with a qualification or less and the grades of managers with a postgraduate degree in the practice of ethical leadership, Who hold a qualification (graduate). In light of the results, the researcher suggested several points, the most important of which is to intensify attention to the areas of training managers in leadership skills, to continuously evaluate the leadership performance of managers, as well as to provide material and moral incentives to managers who are characterized by high leadership skills..